ANALISIS QUALITY FUNCTION DEPLOYMENT (QFD) : THE VOICE OF CUSTOMER UNTUK MENGHASILKAN KUALITAS JASA (Studi kasus pada PT. Kereta Api Indonesia) - Sabihaini Sabihaini; Andi Yulianto (Universitas Trisakti, 2003)
OFD analysis applied in industrial manufacture is emphasizing the use of matrix approach. On the other hand, QFD analysis in the service sectors is utilizing the combination of Service Quality (Serqual) Dimensions and QFD itself. This combination will come up with a result of a House of Service Quality (HOSQ) Approach. Based on the result of QFD analysis by con- stucting the House of Quality, it was found that mostof the consumer attributes concemed as importantand mostimportant.